2008
DOI: 10.1038/nm1757
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell activators: a new class of highly effective vaccine adjuvants

Abstract: Mast cells (MCs) have recently received recognition as prominent effectors in the regulation of immune cell migration to draining lymph nodes and lymphocyte activation. However, their role in the development of humoral immune responses is not clear. Here, we demonstrate that subcutaneous or nasal administration of small-molecule MC activators with vaccine antigens evokes large increases in antigen-specific serum immunoglobulin G (IgG) responses. These responses were MC dependent and correlated with increased d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
194
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(204 citation statements)
references
References 35 publications
9
194
1
Order By: Relevance
“…Although studies are needed on the role of MCs in generation of Agspecific immunity, the studies reported here show that MCs have a role in the effect of IL-18 as an adjuvant and in augmentation of the CTL response induced by IL-33 as a nasal vaccine adjuvant. MC activators (e.g., compound 48/80) have been reported to stimulate protective immune responses against infections (28,32). In addition, these immune responses are correlated with DC trafficking and lymphocyte recruitment to draining lymph nodes (DLN).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies are needed on the role of MCs in generation of Agspecific immunity, the studies reported here show that MCs have a role in the effect of IL-18 as an adjuvant and in augmentation of the CTL response induced by IL-33 as a nasal vaccine adjuvant. MC activators (e.g., compound 48/80) have been reported to stimulate protective immune responses against infections (28,32). In addition, these immune responses are correlated with DC trafficking and lymphocyte recruitment to draining lymph nodes (DLN).…”
Section: Discussionmentioning
confidence: 99%
“…11 Therefore, recently, people have started to study the efficacy of MC activator C48/80 as an adjuvant, and C48/80 has been shown to be a potential mucosal adjuvant. Just like other mucosal adjuvants, C48/80 as a nontoxic nasal adjuvant 12 can also induce effective sIgA at the mucosal location, and clear the virus in the early stage of pathogen invasion, playing an immunological effect. However, up to now, the mechanism of action of C48/80 adjuvant has not been fully explored, and the related reports on C48/80 as an adjuvant in influenza vaccine were also very few.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C48/80 has also been confirmed as a nontoxic nasal adjuvant. 12 In this study, the NP protein was expressed using E. coli expression system and then purified as a subunit vaccine, and was immunized intranasally to mice in combination with C48/80 adjuvant. It was found that NP, as a candidate vaccine, could protect mice against the influenza virus challenge, and that C48/ 80 adjuvant could significantly enhance the protective effect of the NP vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Local hyperthermia increased the infiltration of leukocytes, including mast cells at the site of tumors (27). The adjuvant activity of C48/80 was associated with its ability to induce DC migration via a mechanism that required mast cells and mast cell-derived TNF (14). Furthermore, McGowen et al reported that C48/80 produced much greater levels of IFN than it did IL-4, IL-5, IL-6 or IL-17, and reduced the IgG1/IgG2a ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 48/80 (C48/80) is a stimulus of mast cell degranulation (12,13). It has been reported that the mast cell activator C48/80 was an effective and safe adjuvant for the induction of anthrax lethal toxin neutralizing antibody responses when delivered intranasally, intradermally or via the footpad to mice with anthrax protective antigen (13,14). However, few studies were found concerning the use of C48/80 in tumor treatment; therefore, in the present study, local hyperthermia combined with C48/80 was applied for melanoma lung metastasis treatment.…”
Section: Introductionmentioning
confidence: 99%